Development and Feasibility Testing of ProProfs-Based Digital Assessment Media to Improve Science Learning Evaluation in Grade IV Elementary Madrasahs - Vita Fitriatul Ulya; Zainal Abidin; Zulfatun Anisah; A.M. Miftah Anshori; M. Syahrul Muharrom (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This research aims to develop and test the feasibility of assessment media for IPAS (Natural and Social Sciences) subjects based on the Proprofs digital application for grade IV MI/SD students. The background of this research is the low motivation of students to learn in the evaluation of IPAS, the majority of whom still use conventional methods (Paper Based Test/PBT), as well as the lack of use of digital media in the IPAS assessment process. This study uses the Borg and Gall model Research and Development (R&D) method which is simplified into three main stages: preliminary study, development and testing, and implementation. The product developed is the Proprofs Quiz Maker digital application. The results of the feasibility test from the validator show that the Proprofs assessment media is included in the criteria of Very Appropriate and Appropriate. In detail, the total percentage of acquisition from material experts is 95% (Very Appropriate), media experts 92.5% (Very Appropriate), and learning evaluation experts 70% (Appropriate), with a total average score obtained from validators of 85.8%. In addition, the results of a small group trial of 41 students in grade IV of MI Al Hidayah Lajukidul also showed an overall score of 94%, which was included in the Very Feasible criteria. Following product revision and subsequent implementation in the main and operational field trials involving a total of 82 students from Grade IV at MI Al-Hidayah, an overall score of 96% was obtained, classified under the Very Appropriate criteria. This demonstrates that the development of Proprofs-based IPAS assessment media is highly feasible, effective, and can significantly increase student motivation and learning outcomes.